Penguatan Literasi Islam Moderat melalui Kajian Kitab Risalat al-Kawakib al-Lamma’ah bagi Santri Kelas Akhir di Pondok Pesantren Bahrul Ulum Tambakberas Jombang - Miftakhul Arif (LP3M IAIFA Kediri, 2026)
The proliferation of extremist religious doctrines has made the reinforcement of moderate Islamic literacy a strategic imperative, particularly for senior santri who are on the threshold of engaging with wider social and academic environments. This program for strengthening moderate Islamic literacy is designed to deepen the santri comprehension of the principles and values of Islamic moderation through a systematic study of Risalat al-Kawakib al-Lamma‘ah authored by KH Abul Fadhol, to cultivate advanced critical thinking capacities, and to solidify their commitment to the ethos of religious moderation. The program involved senior santri from Madrasah Aliyah Unggulan KH Wahab Hasbullah, Bahrul Ulum Islamic Boarding School, Tambakberas, Jombang. A service-learning approach was adopted as the primary methodological framework, implemented across three sequential phases: pre-implementation, implementation, and post-implementation. The learning activities were conducted through structured textual analysis and participatory, dialogical discussions. The findings demonstrate a substantive increase in the santri conceptual understanding of moderate Islam as articulated in Risalat al-Kawakib al-Lamma‘ah, alongside measurable improvements in their critical reasoning skills and a strengthened normative commitment to the practice of religious moderation.